E-Government Stage Model Pada Website Layanan Aspirasi Digital Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Kudus - Anne, Anne; Nugraha, Joko Tri; Winanta, Rizza Arge; Widyantoro, Sigid (Innovative: Journal Of Social Science Research, 2025)
The development of e-government is a key focus in realizing transparent, effective, and participatory governance. This study aims to analyze the maturity level of the Ladeni Rakyat digital service by DPRD Kudus Regency and identify supporting and inhibiting factors in its development. This research employs a qualitative approach using a case study method and purposive as well as snowball sampling techniques. Informants include platform administrators, technical staff, and service users. The analysis refers to the five pillars of e-government maturity by Fietkiewicz et al.: Information Dissemination, Communication, Transaction, Interoperability, and Participation. The findings show notable progress in Communication and Transaction aspects. However, there are deficiencies in Information Dissemination, Interoperability, and Participation. Enhancing information dissemination, cross-service integration, and public participation is necessary to achieve optimal e-government maturity.